Perspectives and Challenges in Doctoral Research Selected Papers from the 10th Edition of the Scientific Conference of the Doctoral Schools of "Dunărea de Jos" University of Galati (SCDS-UDJG) - Rusu, Eugen; Rapeanu, Gabriela (MDPI - Multidisciplinary Digital Publishing Institute, 2023)
This reprint includes papers from different research fields, reflecting the sectional talks presented at the 10th edition of the Scientific Conference of the Doctoral Schools of "Dunărea de Jos" University of Galaţi, which took place in June 2022. The objective of the 2022 Conference was to bring together perspectives and challenges in doctoral research in a common forum and to provide a platform enabling doctoral researchers to meet and share state-of-the-art developments in their fields. It comprises 13 papers presented at the conference from several fields, including mechanical and industrial engineering, food science and biotechnology, electrical/electronic engineering, systems engineering and information technologies, chemistry, electrochemistry, and economic models and strategies.